MAKNA PERKAWINAN PASANGAN BEDA AGAMA DI KOTA BANDUNG - Linda Tunaerah (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
Islam regulates all aspects of human life from the smallest to the largest, from the simplest to the most complex. There are so many arguments that exist in the Qur'an and hadith that Islam regulates all aspects of human life. Even the slightest thing cannot be separated from the attention of Islam, including the communication of dakwaj to families of different religions, starting from interfaith marriages to forming and giving birth to interfaith families. Although according to Islamic law, interfaith marriages are prohibited, but in everyday life many interfaith marriages form interfaith families. Many factors cause interfaith marriages, causing conflicts that occur in interfaith families. The most important thing is about communication in interfaith families, communication is the most important thing in all things, including in the family, so there are several things that must be considered in communicate with families of different religions. One of them is how to communicate da'wah within the family. The method used in this research uses qualitative research methods using the phenomenological theory of Alfred Schuzt and data collection methods using non-participant observation and in-depth interviews and is equipped with triangulation methods as a test of the results of interviews with key informants. The purpose of this study is that researchers want to know how the causes of interfaith marriages occur and how the communication patterns in interfaith families are.